2022
DOI: 10.3390/molecules27072185
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Cordia dichotoma against a Panel of Human Cancer Cell Lines and Their Phytochemical Profiling via HPLC and GCMS

Abstract: The current study was conducted to examine the in vitro anticancer potential of Cordia dichotoma (bark, leaves, pulp and seed). The plant material was collected from UT of J&K and methodical bioassays were carried out on ten human cancer cell lines (Michigan Cancer Foundation-7 (MCF-7), M.D. Anderson-Metastatic Breast (MDA-MB-231), Neuroblastoma-2a (N2A), SH-SY5Y, U-251, HCT-116, SW-620, A-549, MIA PaCa-2, Panc-1) from five different origins (breast, CNS, colon, lung, pancreas) respectively. Methanolic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Interestingly, these compounds were found in significant amounts in the methanol extract from the leaves and stems of C. silvatica, except cis -5,8,11,14,17-eicosapentaenoic acid, which was only detected in the leaves. c is -Vaccenic acid and trans -13-octadecenoic acid were also reported to have antitumor properties [ 33 , 34 ]. Importantly, cis -vaccenic (RA = 38.32%) and trans -13-octadecenoic acid (RA = 25.06%) ( Table 1 and Figure 1 ) were found in the leaves and stems, respectively, in a greater amount than other detected compounds of methanol extract from C. silvatica ( Table 1 and Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these compounds were found in significant amounts in the methanol extract from the leaves and stems of C. silvatica, except cis -5,8,11,14,17-eicosapentaenoic acid, which was only detected in the leaves. c is -Vaccenic acid and trans -13-octadecenoic acid were also reported to have antitumor properties [ 33 , 34 ]. Importantly, cis -vaccenic (RA = 38.32%) and trans -13-octadecenoic acid (RA = 25.06%) ( Table 1 and Figure 1 ) were found in the leaves and stems, respectively, in a greater amount than other detected compounds of methanol extract from C. silvatica ( Table 1 and Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the results can be different from one cancer type to another even though they have many common features, though each single cancer type has its own proliferation and invasion pathway. It has been demonstrated that different outcomes of different cell line types even with treatment of the same preparation of extract ( Lamdan et al, 2020 , Keta et al, 2020 , Raina et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the discovery of new and effective sources of natural constituents has attracted the attention of the scientific community, despite the recent progress in the synthesis of new anticancer agents [10]. This fact is confirmed by studies revealing that naturally occurring compounds such as terpenoids, phenolics, flavonoids, and alkaloids exert significant antitumor potential [11].…”
Section: Introductionmentioning
confidence: 99%